2015
DOI: 10.1002/elsc.201400131
|View full text |Cite
|
Sign up to set email alerts
|

Green bioprinting: Viability and growth analysis of microalgae immobilized in 3D‐plotted hydrogels versus suspension cultures

Abstract: Biotechnological processes using photosynthetic microorganisms are of growing industrial interest for the production of renewable energies, platform chemicals or pharmaceutical drugs. Microalgae can be cultivated in suspension, or immobilized by active or passive approaches. We analyzed microalgae growth and population dynamics at different temperatures and illumination conditions in suspension and immobilized in 3D-plotted hydrogels. For microbial processes, the viability of the organisms is essential as prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…32 Apart from bioprinting of mammalian cells, it was previously shown that the blend of alginate and mc forms a bioink which is suitable for Green Bioprinting of micro algae. [48][49][50] The micro algae could be bioprinted alone and in coculture with mammalian cells in alginate-mc. 48 Crucially, the microalgae did not lose their photosynthetic activity after fabrication and thus might be able to provide oxygen needed by the surrounding mammalian cells.…”
Section: Development Of Novel Bioinks Including Methylcellulosementioning
confidence: 99%
“…32 Apart from bioprinting of mammalian cells, it was previously shown that the blend of alginate and mc forms a bioink which is suitable for Green Bioprinting of micro algae. [48][49][50] The micro algae could be bioprinted alone and in coculture with mammalian cells in alginate-mc. 48 Crucially, the microalgae did not lose their photosynthetic activity after fabrication and thus might be able to provide oxygen needed by the surrounding mammalian cells.…”
Section: Development Of Novel Bioinks Including Methylcellulosementioning
confidence: 99%
“…In vitro Therapeutic drugs [151] Green microalgae Chlamydomonas reinhardtii Co-culture with mammalian cells…”
Section: Alginate Hydrogelmentioning
confidence: 99%
“…[150] By using 3D bioprinting of cells into scaffolds, C. reinhardtii and C. sorokiniana microalgae were imbedded in a highly structural organization alginate-based hydrogel scaffold. [151] 3D bioprinting has emerged as a viable technique to design and create scaffolds embedded with cells for tissue and organ growth with clinically relevant size, shape, and structural integrity. [152] This involves a computer-controlled 3D printer able to transform a computer aided design into rapid and high-precision construction of 3D biological structures using an appropriate bioink (Figure 17A).…”
Section: Phytoplankton-mammalian Cell Co-cultures Inside 3d Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations